Harmonisasi Kewenangan Penyidikan Personel Tentara Nasional Indonesia yang Melakukan Tindak Pidana Korupsi - Zulmi, Muhammad Nizar; Shinta Hadiyantina; Muktiono (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to analyze the legal implications of disharmony of authority between the Corruption Eradication Commission (KPK) and the Indonesian National Army Military Police Center (Puspom TNI) in investigating corruption perpetrators from military personnel as well as the ideal formulation in the investigation of corruption cases from the perspective of the principle of equality before the law in the future. This research is normative juridical research that uses both the statutory and conceptual approaches. This study concludes two things. First, the resolution of the disharmony of authority between the KPK and Puspom TNI in the 2002 KPK Law, the Military Justice Law, and the TNI Law is that the legislators harmonize the regulatory material, submit a request for judicial review of the law in the Mahkamah Konstitusi, and apply the principle of lex specialis derogat legi generalis. Second, the ideal formulation for the future is to revise the Military Justice Law and the TNI Law, which specifically regulates TNI soldiers who commit military crimes only. If a soldier commits a corruption crime, the Corruption Court will resolve the case without distinguishing the perpetrator's military or civilian status.